What is enlightened agriculture? A multi-normative approach to the nature and values of food production systems - Gunton, Richard M. (Frontiers in Sustainable Food Systems, 2023)
The sustainable development of farming is an agenda with strong normative undertones, yet beyond the call to combine enhanced agricultural output with better environmental outcomes, this normativity is rarely unpacked or analysed with respect to different worldviews and value systems. The normative practices approach is a values-explicit framework for analysing the normativity of social practices; here it is applied to agriculture to provide a critique of sustainability. This helps to clarify the nature of farming and the breadth of sometimes incommensurable visions for its sustainable intensification. It also leads to a values-explicit concept of ‘enlightened agriculture’, defined as models for agricultural systems that explicitly realise aesthetic, jural and moral benefits, possibly at some cost to economic productivity. While any implementation of this qualitative definition will be worldview-dependent, it appears that land-sparing approaches and the promotion of biodiversity per se are unlikely to qualify as enlightened farming, but farming with concern for the wellbeing of humans and nonhumans probably does. The recognition that normative worldviews direct social practices implies that there will be profound diversity among visions of good farming, which technical and political proposals ought to account for. In the face of accelerating global change, this diversity may provide both resilience and fertile grounds for new context-sensitive and community-led initiatives.